Unenhanced CT imaging is highly sensitive to exclude pheochromocytoma: a multicenter study. Issue 5 (May 2018) - Buitenwerf, Edward; Korteweg, Tijmen; Visser, Anneke; Haag, Charlotte M S C; Feelders, Richard A; Timmers, Henri J L M; Canu, Letizia; Haak, Harm R; Bisschop, Peter H L T; Eekhoff, Elisabeth M W; Corssmit, Eleonora P M; Krak, Nanda C; et al.
Abstract : Background: A substantial proportion of all pheochromocytomas is currently detected during the evaluation of an adrenal incidentaloma. Recently, it has been suggested that biochemical testing to rule out pheochromocytoma is unnecessary in case of an adrenal incidentaloma with an unenhanced attenuation value ≤10 Hounsfield Units (HU) at computed tomography (CT). Objectives: We aimed to determine the sensitivity of the 10 HU threshold value to exclude a pheochromocytoma. Methods: Retrospective multicenter study with systematic reassessment of preoperative unenhanced CT scans performed in patients in whom a histopathologically proven pheochromocytoma had been diagnosed. Unenhanced attenuation values were determined independently by two experienced radiologists. Sensitivity of the 10 HU threshold was calculated, and interobserver consistency was assessed using the intraclass correlation coefficient (ICC). Results: 214 patients were identified harboring a total number of 222 pheochromocytomas. Maximum tumor diameter was 51 (39–74) mm. The mean attenuation value within the region of interest was 36 ± 10 HU. Only one pheochromocytoma demonstrated an attenuation value ≤10 HU, resulting in a sensitivity of 99.6% (95% CI: 97.5–99.9). ICC was 0.81 (95% CI: 0.75–0.86) with a standard error of measurement of 7.3 HU between observers. Conclusion: The likelihood of a pheochromocytoma with an unenhanced attenuation value ≤10 HU on CT is very low. The interobserver consistency in attenuation measurement is excellent. Our study supports the recommendation that in patients with an adrenal incidentaloma biochemical testing for ruling out pheochromocytoma is only indicated in adrenal tumors with an unenhanced attenuation value >10 HU.